Customizing Component Regulated Dense Heterointerfaces for Crafting Robust Lithium‐Sulfur Batteries. (19th December 2022) - Zhao, Mincai; Tan, Pengcheng; Cai, Daoping; Liu, Yangjie; Zhang, Chaoqi; Fei, Ban; Sa, Baisheng; Chen, Qidi; Zhan, Hongbing
Abstract: Lithium–sulfur (Li–S) batteries hold great promise for the next‐generation energy storage system. However, their commercial applications are severely hindered by myriads of drawbacks such as poor electrical conductivity of sulfur, sluggish redox reaction kinetics of sulfur species, "shuttling effect" of soluble lithium polysulfides (LiPSs) and uncontrollable dendritic Li growth. Herein, it is conceptually demonstrated that sluggish conversion kinetics of LiPSs is markedly stimulated by exquisite heterointerface modulation at nanoscale level over transition metal carbides and nitrides. In this scenario, N‐doped carbon coupled with molybdenum nitride/carbide (Mo2 N‐MoC/NC) hybrid nanocomposites are designed through a one‐step carbonization‐nitridation process, wherein component regulation induced dense heterointerfaces are in situ produced. Benefiting from high electrical conductivity, strong chemical adsorption, and superior catalytic activity afforded by dense heterointerfaces, the Mo2 N‐MoC/NC modified separators significantly restrict the soluble LiPSs shuttling and simultaneously suppress the Li dendrite generation. The assembled Li–S batteries with Mo2 N‐MoC/NC modified separators exhibit remarkable electrochemical performance. Integrated experimental and theoretical results substantiate the boosted chemisorption and catalytic conversion of LiPSs endowed by such dense heterointerfaces. The work will open a new vista for rationally constructing multifarious heterostructured materials for the communities of Li‐S batteries. Abstract : This work conceptually demonstrates that sluggish conversion kinetics of lithium polysulfides is markedly stimulated by exquisite heterointerface modulation at nanoscale level over molybdenum carbides and nitrides. Experimental and theoretical results substantiate the boosted chemisorption and conversion of lithium polysulfides endowed by dense heterointerfaces. The work will open a new vista for rationally constructing multifarious heterostructured materials for lithium–sulfur batteries.